Rheology, acceptability and texture of wheat flour tortillas supplemented with soybean residue - Montemayor-Mora, Gabriela (J Food Sci Technol, 2018)
Dry soybean (Glycine max) residue (SBR) is a byproduct rich in dietary fibre and protein with high levels of essential amino acids. The effects due to the substitution of refined wheat flour with 5% or 10% SBR in dough rheology and hot-press tortilla texture, dimensions, colour, protein and dietary fibre contents were studied. Substitution of 10% SBR improved flour in terms of gluten strength and sedimentation without significantly affecting dough hardness, cohesiveness, adhesiveness, and extensibility. The dimensions, colour and sensory acceptance of the supplemented tortillas were not affected by the addition of the SBR. The 10% SBR tortillas contained 1.77 times more insoluble dietary fibre, protein content of 9.3%, in vitro protein digestibility of 84% and protein digestibility corrected amino acid score (PDCAAS) of 52.63%. Results indicated that wheat flour tortillas with 10% SBR an excellent alternative to regular counterparts owing to their higher dietary fibre and protein quantity and quality.